ANALISIS METODE PEMBAYARAN DALAM MENINGKATKAN MINAT BELI KONSUMEN PADA E-COMMERCE: TINJAUAN PERSPEKTIF EKONOMI ISLAM - Annisa Nur Ramadhani; Muhammad Iqbal Fasa; Suharto Suharto (Jurnal Bina Bangsa Ekonomika, 2022)
In the world of e-commerce can not be separated from the name of the payment method. Currently, payment methods have been improved to make it easier for consumers. There are various payment methods, so consumers can choose which method to use. Broadly speaking, the payment methods are divided into two, namely cash and non-cash payments. Islam is also here to provide guidance for all aspects of our lives. One of them is buying and selling transactions which are included in the field of muamalah. The research method used is the Library Study Method. The author tries to collect information and data that are in accordance with the topic. The author collects and studies theoretical data sourced from reference books, scientific works, theses, and the internet and other sources. The purpose of this study was to find out the role of payment methods in increasing consumer interest in e-commerce in terms of Islamic economics